Answer:
a. x × (y + z) = -13/240
c. x × (y × z) = 1/24
Explanation:
The given values of the variables are;
![x = (-1)/(8) , y = (-2)/(5) \ and \ z = (10)/(12)](https://img.qammunity.org/2022/formulas/mathematics/high-school/znqjher3w77k17xhrujp81qd0lyeisi3th.png)
a. x × (y + z) = (x × y) + (x × z), by distributive property
Plugging in the values gives;
![(-1)/(8) * \left ((-2)/(5) + (10)/(12) \right) = \left ( (-1)/(8) *(-2)/(5) \right) + \left ( (-1)/(8) * (10)/(12) \right)](https://img.qammunity.org/2022/formulas/mathematics/high-school/71kz3l4d1d19oxui0xbniiydxj4j8mvf1m.png)
![(-1)/(8) * \left ((-2)/(5) + (10)/(12) \right) = (-1)/(8) * \left ((13)/(30) \right) = (-13)/(240)](https://img.qammunity.org/2022/formulas/mathematics/high-school/ltw4b1x1tpcnc98ebkqxq4f75hdthdn48a.png)
![\left ( (-1)/(8) *(-2)/(5) \right) + \left ( (-1)/(8) * (10)/(12) \right) = (1)/(20) + (-5)/(48) = (-13)/(240)](https://img.qammunity.org/2022/formulas/mathematics/high-school/zn2vu9ucbpblznzlqfjx8mzim5x1ddn0qb.png)
Therefore;
![(-1)/(8) * \left ((-2)/(5) + (10)/(12) \right) = \left ( (-1)/(8) *(-2)/(5) \right) + \left ( (-1)/(8) * (10)/(12) \right) = (-13)/(240)](https://img.qammunity.org/2022/formulas/mathematics/high-school/73xettxiqw5fn6cqsces6mnegscez7zx7w.png)
c. x × (y × z) = (x × y) × z
Plugging in the values for 'x', 'y', and 'z' gives;
![(-1)/(8) * \left ((-2)/(5) * (10)/(12) \right) = \left ( (-1)/(8) *(-2)/(5) \right) * \left ( (10)/(12) \right) = (1)/(24)](https://img.qammunity.org/2022/formulas/mathematics/high-school/phjuqui0ukh71fd2f9ds0w7xjewy9cuz36.png)